Structure and electrochemistry of K-ion Prussian blue analogues - Cattermull, J (2024)
Rechargeable batteries are the pivotal technology for the electrification of energy and transport infrastructure. Prussian blue analogues (PBAs) are an increasingly prominent family of cathode materials for Na- and K-ion batteries, a cheaper and more sustainable alternative to Li-ion batteries. As molecular framework materials, PBAs are structurally distinct from more established layered oxide or polyanionic cathode materials. Structurally, PBAs are most closely related to perovskites, and as yet it is not clear how PBA electrochemistry relates to other cathode materials from this structural perspective.